Predicting short-term (30-day) mortality in patients with ischemic stroke using the baseline score of the National Institutes of Health Stroke Scale: Lestvica NIHSS (National Institutes of Health Stroke Scale) in kratkoročna (30-dnevna) umrljivost bolnikov z ishemično možgansko kapjo - Hojs Fabjan, Tanja (Acta Medico-Biotechnica, 2021)
Purpose: The National Institutes of Health Stroke Scale (NIHSS) was developed to measure neurologic outcome and recovery in patients with stroke. The aim of our study was to establish the validity of the NIHSS on short-term (30-day) mortality in patients with ischemic stroke. Methods: All 402 patients (216 males) with acute ischemic stroke hospitalized over 1 year were included in the study. Information on the presence of diabetes mellitus and smoking habits was obtained by a questionnaire. Systolic and diastolic blood pressure was measured upon hospital admission. The body mass index was calculated. Laboratory data were assessed in the first 24h after stroke onset. The National Institutes of Health Stroke Scale (NIHSS) was employed upon hospital admission. Patients were then followed up for 30 days. Results: The mean age of patients was 70.89 years (range, 36–96 years). Women were older than men (P<0.0001). There were 49 (12.2%) deaths in the first 30 days. Patients who died had a higher NIHSS score upon hospital admission (P=0.0001), were older (P=0.013), had higher high-sensitivity C-reactive protein (hsCRP) levels (P=0.0001) and lower albumin levels (P=0.016). With Cox multivariable regression analyses, NIHSS score (P=0.0001) as well as levels of total cholesterol (TC) (P=0.004) and low-density lipoproteincholesterol (LDL-C) (P=0.016) were predictors of 30-day mortality. After the addition of age as a variable, NIHSS score (P=0.0001) as well as levels of TC (P=0.006) and LDL-C (P=0.025) remained predictors of mortality. Conclusion: The NIHSS is a good predictor of outcome in short-term (30-day) mortality in patients with ischemic stroke.